Assessing Information Processing in Capital Market Structures - Bakri , Muhammad; Andriani, Dian; Bahri, Syamsul (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2024)
This study investigates the evolving landscape of alternative investment markets, seeking to understand trends, challenges, and implications for investors and market dynamics. Through a comprehensive research design and methodology involving literature review and empirical analysis, the study reveals a notable surge in investor interest in alternative assets, driven by the quest for diversification and higher returns amid market volatility. However, alongside this trend, the research identifies challenges such as complexity, opacity, and liquidity constraints inherent in many alternative investment strategies. Findings underscore the critical importance of rigorous due diligence, manager selection processes, and regulatory oversight in mitigating risks associated with alternative investments. Moreover, the discussion delves into the intricate interplay between market microstructure, information dissemination, and investor behavior, elucidating the role of efficient information processing mechanisms in maintaining market efficiency and liquidity. The study's implications extend to investors and regulators, emphasizing the need for investors to cultivate a robust understanding of alternative asset classes and the importance of regulatory frameworks in safeguarding investor interests and market integrity. Overall, the study contributes to the broader discourse on alternative investments and underscores the imperative for stakeholders to navigate the complexities of these markets effectively in an ever-changing financial landscape